2022
DOI: 10.1016/j.eats.2021.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Technique for Reduction and Fixation of an Acetabular Rim Fracture

Abstract: Acetabular rim fractures can accompany patients with femoroacetabular impingement. Frequently, the acetabular rim fracture is excised. However, if the osseous fragment of the acetabular rim fracture is large enough to result in instability, then the acetabular rim fracture should be reduced and secured with internal fixation. The purpose of this technical note was to describe the arthroscopic technique of internal fixation of an acetabular rim fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Pérez et al 12 and DeFroda et al 13 reported the suture-on-screw technique for os acetabuli fixation and labral repair simultaneously. Essilfie et al 14 reported a hybrid technique to fix acetabular rim fractures and labrums with metal screws and suture anchors, respectively. This technique theoretically provides rigid fixation for os acetabuli, but it also has some drawbacks, first, it could be a technical challenge to perform an arthroscopic fixation using common instruments of routine traumatic orthopaedics.…”
Section: Discussionmentioning
confidence: 99%
“…Pérez et al 12 and DeFroda et al 13 reported the suture-on-screw technique for os acetabuli fixation and labral repair simultaneously. Essilfie et al 14 reported a hybrid technique to fix acetabular rim fractures and labrums with metal screws and suture anchors, respectively. This technique theoretically provides rigid fixation for os acetabuli, but it also has some drawbacks, first, it could be a technical challenge to perform an arthroscopic fixation using common instruments of routine traumatic orthopaedics.…”
Section: Discussionmentioning
confidence: 99%